A new fuzzy granular technique for the condition monitoring of electrical hotspots based on infrared thermography - Ahmed, M. M.; Kamal Z., Zamli; Nazmul Huda, A. S.; Nor Ashidi, Mat Isa; M. Nomani, Kabir (2018)
In Malaysia, more than 46% of the total causes of fires in buildings are because of the failure of electrical distribution (Ref: http://www.bomba.gov.my). Infrared thermography technology is currently being used in various applications, including fault diagnosis in electrical equipment. Thermal abnormalities are diagnosed by identifying and classifying the hotspot conditions of electrical components. The proposed intelligent system is applied to automatically realize and formulate the conditions of the thermal abnormalities. On the basis of the priority level, the hotspot conditions are categorized as normal, warning, and critical.